Сади Боболі у Флоренції як взірець садів Італії епохи ренесансу - Kosenko, I.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
On the basis of literary data and own investigations the concept description of Italy gardens during the Renaissance epoch and the history of creation, development and conservation of Boboli gardens in Florence is stated briefly.